Bauran Pemasaran Pendidikan Dalam Meningkatkan Minat Siswa Baru Di Kun Anta Preschool - Nurhikma Yanti; Maskuri Sutomo; Elimawaty Rombe; Risnawati Risnawati (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Competition in the education sector is currently quite high, requiring schools to be able to implement educational strategies that are innovative, effective and efficient. This research aims to determine the strategies used by Kun Anta Prescholl in an effort to increase the interest of new students. The research method used is qualitative descriptive research, because it aims to understand information about a research object comprehensively and according to needs. The results of this research show that the marketing mix strategy is very effective in increasing the interest of new students at Kun Anta Preschool.